Capital Breeding in a Diapausing Copepod: A Transcriptomics Analysis - Roncalli, Vittoria; Cieslak, Matthew C.; Hopcroft, Russell R.; Lenz, Petra H. (Frontiers in Marine Science, 2020)
Capital breeders must balance the energetic requirements of cellular function and the cost of reproduction. The subarctic copepod Neocalanus flemingeri, a small planktonic crustacean, depends on a short annual phytoplankton bloom to acquire the energy needed to support a non-feeding adult female that enters a period of diapause prior to spawning 5 to 7 months later. After emergence from diapause, the reproductive program takes 2 months starting with germline development. In this study, the regulation of genes involved in energy utilization and cellular maintenance were investigated using RNA-Seq as females progressed from diapause to end-of-life. Hierarchical clustering of expression profiles from 61 individual females identified four major transitions in transcriptional profiles along a timeline spanning from diapause to spawning and post-reproduction. The clusters were analyzed statistically for differential gene expression followed by functional analyses. The transition from diapause to post-diapause (early to mid-oogenesis) was characterized by the up-regulation of genes involved in cellular homeostasis, glycolysis and lipid catabolism. As females approached spawning genes involved in cellular homeostasis, like innate immunity became down-regulated. Genes involved in protein ubiquitination and programmed cell death became up-regulated as females started to spawn. Gene expression patterns suggest that energy allocation and utilization is highly dynamic in N. flemingeri during the progression of the reproductive period. Major changes in the expression of genes involved in cellular homeostasis, metabolic processes and autophagy were linked to stages of egg maturation. Changes in gene expression that marked the transition from diapause to post-diapause were similar to those reported in other arthropods that resume feeding after emergence from diapause. As egg maturation progressed, gene expression patterns indicate that resources became concentrated on provisioning eggs, while being diverted away from cellular homeostasis. The data suggest that in N. flemingeri genes are regulated such that organismal function and sources of energy are synchronized with stages of egg maturation to optimize the exploitation of finite resources. The existence of mechanisms that regulate fecundity to match the availability of stored resources could reduce reproductive failure in this species.